Advances in thermofluids : selected, peer reviewed papers from the 5th International Meeting of Advances in Thermofluids (5th IMAT), November 12-13, 2012, Bintan Island, Indonesia - Wahid, Mazlan Abdul (Applied mechanics and materials, 2013)
The book aimes at bringing together the current knowledge of academicians, researchers and scholars from all over the world on all aspects of Thermodynamics, Fluid Mechanics, Heat Transfer and Thermal Engineering. In addition to the fundamentals of thermal phenomena and traditional thermal applications, the contributions also address the emerging domains of thermal transport in fishery, building nano-materials, bio-systems, microsystems, power generation, and energy conversion devices. IMAT was initiated in Southeast Asia, but organizers invite academicians, researchers, and scholars from arou.